Nilai-Nilai Budaya dalam Tradisi Gotong Royong Masyarakat Suku Dayak di Rumah Betang Ensaid Panjang - Haris Firmansyah (Universitas Hamzanwadi, 2023)
The Dayak tribe maintains the tradition of mutual cooperation by living in Betang houses. This Betang house provides an overview of the life of the Dayak Desa community, who live peacefully with existing cultural values, especially regarding the mutual cooperation tradition found in the Ensaid Panjang Betang house. This study aims to describe and find out what cultural values are contained in the mutual cooperation tradition of the Dayak people at Rumah Betang Ensaid Panjang. The research method used is descriptive qualitative research, where researchers obtain results with findings in sentences and words obtained by observation and interviews. The results of this research are that Ensaid Panjang's Betang House is a traditional Dayak house in Sintang, West Kalimantan. House The physical form of this house is a platform, and there are high stairs to climb this betang house. At present, there is only one more traditional Ensaid house left, and it is occupied by some of the people of Ensaid Panjang village. The mutual cooperation values in Betang Ensaid Panjang's house must be put to good use in the lives of the people of West Kalimantan, especially to mobilize community solidarity.